Bioethical Quandaries during the Period of a Pandemic (Global Journal of Human-Social Science, 2021)
The period of the pandemic gave rise to multiple and intractable bioethical quandaries arising In the context of the present study we will limit ourselves to the examination of the critical issues of mandatory vaccination to manage the pandemic compulsory medical testing including temperature screening of the population the use of experimental drugs making the wearing of face masks mandatory and the individual responsibility of each of us for the prevention of the pandemic Participation stresses the importance of education in bioethics Accordingly it supports the notion that once we win the fight for life and health constitutional lawyers ought to take the reins and determine that the character of restrictive measures and healthcare policies adopted in periods of crisis when a prime opportunity for their formulation presented itself because of the pandemic is one of extraordinariness